Wasteland Utilization for B. balcooa Cultivation: Socio-economic and Environmental Impacts through Bamboo-based Product Development. Issue 4 (2019) - Patel, Beena; Gami, Bharat; Patel, Akash; Patel, Pankaj
No abstract available